Changes in blood pressure and arterial stiffness monitored using the cardio–ankle vascular index during hemodialysis - Sato, Shuji; Shimizu, Kazuhiro; Takahashi, Mao; Masai, Motoyuki; Nagakawa, Osamu; Uchino, Junji; Suzuki, Toshihiro; Sato, Yuka; Iwai, Noriko; Shirai, Kohji (Frontiers in Physiology, 2023)
During hemodialysis (HD), blood pressure (BP) changes are frequently observed. However, the mechanism of BP changes during HD has not been fully clarified. The cardio–ankle vascular index (CAVI) reflects the arterial stiffness of the arterial tree from the origin of the aorta to the ankle independent from BP during measurement. Additionally, CAVI reflects functional stiffness in addition to structural stiffness. We aimed to clarify the role of CAVI in regulating the BP system during HD. We included 10 patients undergoing 4-hour HD (total 57 HD sessions). Changes in the CAVI and various hemodynamic parameters were evaluated during each session. During HD, BP decreased and CAVI significantly increased (CAVI, median [interquartile range]; 9.1 [8.4–9.8] [0 min] to 9.6 [9.2–10.2] [240 min], p < 0.05). Changes in CAVI from 0 min to 240 min were significantly correlated with water removal rate (WRR) (r = -0.42, p = 0.002). Changes in CAVI at each measurement point were negatively correlated with ΔBP (Δsystolic BPeach MP, r = -0.23, p < 0.0001; Δdiastolic BPeach MP, r = -0.12, p = 0.029). Whereas one patient exhibited a simultaneous decrease in BP and CAVI during the initial 60 min of HD. Arterial stiffness monitored with CAVI generally increased during HD. CAVI elevation is associated with decreased WWR and BP. An increase in CAVI during HD may reflect the contraction of smooth muscle cells and play an important role in BP maintenance. Hence, measuring CAVI during HD may distinguish the cause of BP changes.